Comparison of the efficacy and tolerability of inhaled hypertonic salines of sodium chloride in pediatric practice - Ilchenko , S.I.; Fialkovska , A.O.; Cherhinets, V.I.; Skriabina , K.V. (Medicni Perspektivi, 2021)
In modern pediatric practice, inhalated hypertonic saline (IHS) is often used for therapeutic and diagnostic purposes. However, the potential development of serious side effects in children is not predicted. The aim of the study was to determine the efficacy and tolerability of IHS of various concentrations in children with cystic fibrosis (CF). The study involved 34 children with CF aged 6 to 18 years (middle age is 13.0±4.4 years). The comparison group consisted of 27 children (middle age is 7.8±2.3 years) without chronic respiratory diseases. The study included three consecutive inhalations. Sterile 0.9% NaCl solution was used for the first inhalation, 3 % NaCl solution – for the second one and 7% NaCl solution – for the third inhalation. For children under 7 years of age, a patented method of obtaining sputum without forced coughing was used. Spirometry was performed before and after each inhalation, and clinical changes were analyzed. It was noted that after inhalation of IHS, the cough in patients became more productive, moist rales were more often heard over the entire surface of the lungs. The activity of induced sputum secretion after inhalation of 3% and 7% NaCl solution did not differ significantly. However, after inhalation of 7% NaCl solution, side effects, such as sore throat, shortness of breath, spastic cough, auscultatory symptoms of bronchospasm were recorded significantly more often compared with lower concentrations of the solution. The decrease in FEV1 was observed in 5.8% of patients after inhalation of 3% NaCl solution and in 11.8% of patients after inhalation of 7% NaCl solution, which was significantly associated with the clinical symptoms of bronchospasm. Inhalation of IHS has an effective mucolytic effect in patients with CF, however, it is necessary to determine the individual sensitivity of the patient to predict a positive therapeutic effect.